The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/famp.12256
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Functional Family Therapy for Adolescent Behavioral and Substance Misuse Problems: A Meta‐Analysis

Abstract: A systematic review of published and unpublished English language articles identified 14 studies containing 18 comparisons between functional family therapy (FFT) and another condition in the treatment of adolescent disruptive behavior and substance use disorders. In 11 of these comparisons, assignment to conditions was random, while nonrandom assignment occurred in seven studies. For both random and nonrandom comparisons, separate meta-analyses were conducted for subgroups of studies depending on the type of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 48 publications
(49 reference statements)
1
42
0
1
Order By: Relevance
“…Positive findings, in the form of reduced reoffending rates, have been reported in Norway (Thøgersen, 2012), and Sweden (Hansson, Cederblad, & H€ o€ ok, 2000). Two studies in Ireland (Graham, Carr, Rooney, Sexton, & Wilson Satterfield, 2014;Hartnett, Carr, & Sexton, 2016) reported success in implementation, as well as significant, sustained reductions in youth behavioral problems. However, a recent RCT conducted in the United Kingdom did not find any differences in reoffending rates or self-reported delinquency between youth who received FFT, relative to those in a comparison group (Humayun et al, 2017).…”
Section: Functional Family Therapymentioning
confidence: 95%
See 1 more Smart Citation
“…Positive findings, in the form of reduced reoffending rates, have been reported in Norway (Thøgersen, 2012), and Sweden (Hansson, Cederblad, & H€ o€ ok, 2000). Two studies in Ireland (Graham, Carr, Rooney, Sexton, & Wilson Satterfield, 2014;Hartnett, Carr, & Sexton, 2016) reported success in implementation, as well as significant, sustained reductions in youth behavioral problems. However, a recent RCT conducted in the United Kingdom did not find any differences in reoffending rates or self-reported delinquency between youth who received FFT, relative to those in a comparison group (Humayun et al, 2017).…”
Section: Functional Family Therapymentioning
confidence: 95%
“…These include truancy (Slesnick & Prestopnik, ), violence (White, Frick, Lawing, & Bauer, ), and substance use (Rhoades, Campbell, & Bumbarger, ). A meta‐analytic study of randomized‐controlled trial (RCT) and quasi‐experimental studies showed support for FFT's overall robustness in mitigating youth delinquent behavior (Hartnett, Carr, Hamilton, & O'Reilly, ). Findings from non‐US sites, however, yield mixed findings.…”
Section: Family Functioning and Youth Offendingmentioning
confidence: 99%
“…Indeed, greater adolescent hostility is related to more externalizing behavior over time (Fosco et al 2014;Glatz et al 2019), which researchers hypothesize may be due to adolescents' hostility influencing parents' interaction style as well, negatively impacting bidirectional family relationships (Glatz et al 2019). For more aversive, chronic conflict, intervention strategies that involve parents or other caregivers are critical to changing both individual behavior and the environment (Hartnett et al 2017).…”
Section: Parent-adolescent Conflict and Risk-takingmentioning
confidence: 99%
“…In a meta‐analysis of 14 studies, Hartnett, Carr, Hamilton, and O'Reilly () concluded that FFT was effective in significantly reducing conduct problems and recidivism rates compared with control conditions or alternative treatments. In a systematic review of 27 clinical trials, Alexander et al.…”
Section: Conduct Disorder and Drug Misusementioning
confidence: 99%
“…In a meta-analysis of 14 studies, Hartnett, Carr, Hamilton, and O'Reilly (2016) concluded that FFT was effective in significantly reducing conduct problems and recidivism rates compared with control conditions or alternative treatments. In a systematic review of 27 clinical trials, Alexander et al (2013) concluded that compared with routine services, FFT was effective in reducing therapy dropout, conduct problems, drug misuse, placement in foster care, and recidivism in adolescents from a variety of ethnic groups over follow-up periods of up to 5 years.…”
Section: Functional Family Therapy (Fft)mentioning
confidence: 99%